Neurodiversity: post-cognitivist foundations of the 3E approach for educational inclusion of autistic students with technology - Ronnie Videla; Ronnie Videla; May Britt Aros; Francisco Parada; Leonie Kausel; Eduardo Sandoval-Obando; Daniela Jorquera; Daniela Jorquera; David Ibacache; Sebastián Maluenda; Pablo Rodríguez-Herrero; Carola Cerpa; et al. (Frontiers in Human Neuroscience)
The concept of neurodiversity has gained strength in the last years to highlight the value of individual differences based on relevant variations in brain functioning. Inclusive education has embraced neurodiversity to promote a culture centered on valuing diversity, in response to clinical models based on deficits or disorders. This theoretical-critical article argues for the need to complement the current foundations of neurodiversity with post-cognitivist perspectives that reaffirm the brain-body-environment continuum, in order to enrich inclusive educational practices for autistic individuals. We begin by reviewing and discussing the concept of neurodiversity and neurocentric arguments in light of post-cognitivism. We then explore the potential of the 3E Cognition approach (embodied, enacted, and environmentally scaffolded) for addressing autism, aiming to provide a holistic understanding that contributes to the practical application of cognitive neuroscience findings in inclusive education. Finally, we present some guidelines and practical cases for creating inclusive educational environments based on digital technologies that enhance agency and sensory multimodality for autistic students.